Digital literacy for learning and academic achievement among students in IIUM - Lubis, Illam Sarima (Kulliyyah of Education, International Islamic University Malaysia, 2018)
Digital literacy is an essential component of learning in the 21st century. The objectives of this study were to identify the levels of digital literacy for learning among university students; examine the differences in students' digital literacy for learning due to demographic variables; and investigate the relationship between digital literacy and student academic achievement. The quantitative method was utilized to answer the research questions. The sample consisted of 273 undergraduate students and 116 postgraduate students selected from the International Islamic University Malaysia (IIUM) -Gombak. The data analysis (i.e. Means, Standard Deviations, Frequencies and Percentages) of the levels of the five dimensions of the digital literacy for learning showed that the 'data presentation skills' dimension scored a high level. However, the other four dimensions (i.e. the information search skills, information retrieval skills, information interpretation skills, and information management skills) indicated moderate levels. The independent sample t-test results showed that there were statistically differences in the means scores for the five dimensions of digital literacy for learning due to the students' level of study and degree. The Spearmen correlation analysis showed no statistically significant relationship between the levels of digital literacy and the student academic achievement. In conclusion, the findings of the study can motivate both teachers and students of IIUM to enhance their digital literacy skills to get better academic achievement.